Enhancing Lecturer Performance: A Meta-Analysis of Organizational Commitment and Transformational Leadership - Sulistiasih Sulistiasih; Widodo Widodo (STAI Hubbulwathan Duri, 2025)
Lecturer performance plays a critical role in achieving institutional goals within higher education. Previous studies suggest that both transformational leadership and organizational commitment significantly impact this performance. However, a comprehensive synthesis of empirical findings is needed to clarify the strength and consistency of these relationships. This study employed a quantitative meta-analysis to examine the effects of transformational leadership and organizational commitment on lecturer performance. A total of 35 empirical studies published between 2020 and 2024 were systematically selected from Scopus, SINTA, and Google Scholar databases. Using JASP version 0.8.4.0, effect sizes were calculated, and heterogeneity was assessed through a random-effects model. The analysis revealed that transformational leadership (r = 0.380) and organizational commitment (r = 0.377) both have a significant positive influence on lecturer performance (p 0.01). Among the two, transformational leadership demonstrated a slightly stronger effect. Moderate heterogeneity was observed across the studies, and no evidence of publication bias was found. These findings align with existing literature, emphasizing the critical role of leadership and organizational commitment in enhancing lecturer performance. The moderate heterogeneity suggests variability in study contexts, yet the overall effect remains robust. The results highlight the value of transformational leadership and organizational commitment in driving lecturer effectiveness in higher education institutions. Practical recommendations include the development of targeted leadership training and institutional policies that foster organizational commitment to improve performance outcomes.